UPAYA PENINGKATAN PENGETAHUAN PADA KADER GAMPONG MEUNASAH INTAN KECAMATAN KUTA BARO KABUPATEN ACEH BESAR DALAM PENCEGAHAN STUNTING - Zahara, Hafni; Lensoni; Kala, Pasyamei Rembune; Anggraini, Yayu; Murni; Saifuddin; Raisah, Putri; Riezky, Ade Kiki (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time. There are around 8-10 children under the stunting category in Meunasah Intan Village, Aceh Besar District. The actions taken by Integrated Healthcare Center (posyandu) cadres are providing counseling about feeding, motor stimulation, and working together with nutrition workers at the puskesmas. This study uses a pre-experimental design type one group pretest-posttest design. The population is Posyandu cadres, Gampong Meunasah Intan, Kuta Baro District, Aceh Besar Regency with 14 cadres. Based on the results of the counseling, it is known that the average level of knowledge of cadres before being given counseling is 9.64 and after being given counseling is 11.50. The level of knowledge of cadres before and after being given counseling experienced a significant increase, namely 0.00 < 0.05. So, it can be concluded that there are differences in the level of knowledge of cadres about stunting prevention before and after being given counseling. This shows that this change is sufficient to improve the knowledge of posyandu cadres about stunting to be used as capital in carrying out monitoring activities for growth and nutritional status at the posyandu, as well as being able to provide counseling to families of children under five who are at risk or experiencing stunting.